A funcionalidade do trabalho improdutivo para a reprodução do sistema capitalista - Pinheiro, Manuella Aragão (2013)
This dissertation is about the functionality of unproductive labor leading to the capital reproduction. The purpose is to explain the genesis and the expansion of unproductive activities in and outside the factory space, as well as how the functionality contributes to the social reproduction dynamics of capital. The bibliography research was resorted through historical rescue of the first capitalist form of organization of production process until the most contemporary. In this way, the theoretical foundation that guided the study were analyzes chaired by Karl Marx, from his critique to the political economy in capitalist society, and Marxist authors who have leaned over the unproductive labor. Work is understood as a central category in the mankind process of self-construction and ineradicable condition of existence of any social formation process. Under the rule of capital, this work is subsumed to abstract alienated labor, which does not produce surplus value. Armed with this ontological conclusion, it is demonstrated with the study that productive labor arises from the explorer peculiar character to the capitalism production and the need for a control to ensure that exploration in a context, mainly marked by opposition ,“as enemies”, between manual and intellectual labor. It is noticed that this control function is transferred to a group of workers as soon as the production becomes truly capitalist. It appears at the same time, the so-called unproductive workers are those whose function, determined by the production process, will be to control the manual labor, assuming different expressions and contours during the capitalism development.